Political and Leadership Practices of The Domaget Indigenous People in Nueva Ecija - Pastorfide, Danilo D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Indigenous Peoples (IPs) play a vital role in preserving cultural her-itage, particularly in the Philippines, where Indigenous Cultural Communities (ICCs) strive to maintain their identities and practices. This study investigates the leadership practices of the Domaget In-digenous Cultural Community in Nueva Ecija through a Descriptive-Quantitative approach, utilizing interviews and survey question-naires. Findings reveal that leadership within the Domaget and Kalanguya IPs is predominantly male, with leaders aged 61–70 years and possessing limited formal education. Leadership roles, including Chieftains, Elders, and Tribal Leaders, are central to governance and cultural preservation, with elders playing pivotal roles in knowledge transfer. The hierarchical structure is led by the "Mangondem," sup-ported by spiritual and governance roles like "Gangot" and "Subka-lan." While the community values peaceful governance and cultural continuity, there is resistance to militaristic defense structures. The study highlights the need for sustainable livelihood opportunities and enhanced knowledge-sharing to foster resilience and social co-hesion.